2008
DOI: 10.1002/hbm.20634
|View full text |Cite
|
Sign up to set email alerts
|

Decreased neural activity in reward circuitry during personal reference in abstinent alcoholics—A fMRI study

Abstract: Two of the most striking features in alcoholism are the irresistible craving for alcohol and the proceeding neglect of other activities and pleasures that were formerly relevant. Craving has been investigated extensively and is commonly due to a dysfunctional reward system. The neural basis of the neglect of self-relevant interests, which can be described as altered personal reference, and its association to the reward system, however, remains unclear. Using fMRI, we investigated neural activity during a parad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 44 publications
7
51
0
1
Order By: Relevance
“…Nevertheless, we remained unable to control for other possible factors like reward. High self-related stimuli may exhibit a higher degree of reward than those that exhibit low self-relatedness because self appears to be related to distinctive activity levels in the reward system (de Greck et al, 2008(de Greck et al, , 2009(de Greck et al, , 2010. Hence, future EEG and MRS studies may be necessary in order to directly compare self-relatedness and reward, as well as to determine how these are modulated by glutamate.…”
Section: Methodological Limitationsmentioning
confidence: 99%
“…Nevertheless, we remained unable to control for other possible factors like reward. High self-related stimuli may exhibit a higher degree of reward than those that exhibit low self-relatedness because self appears to be related to distinctive activity levels in the reward system (de Greck et al, 2008(de Greck et al, , 2009(de Greck et al, , 2010. Hence, future EEG and MRS studies may be necessary in order to directly compare self-relatedness and reward, as well as to determine how these are modulated by glutamate.…”
Section: Methodological Limitationsmentioning
confidence: 99%
“…In a preliminary study by our group, tasks of high personal relevance induced neuronal activity in exactly the regions implicated in reward function in healthy subjects [de Greck et al, 2008]. Recently, our group also found that alcoholic patients showed decreased neuronal activity in reward circuitry (i.e., left and right NACC/VS, VTA, VMPFC) during the evaluation of stimuli with a high personal relevance as compared to healthy controls [de Greck et al, 2009] showing that the apparent changes in behavior stem from a lack of activation in reward circuitry during the evaluation of stimuli of high personal relevance.…”
Section: Introductionmentioning
confidence: 94%
“…Patients are increasingly preoccupied by gambling and so begin to neglect other formerly self-relevant stimuli and behaviors. Psychologically, the evaluation of personal relevance or self-relatedness, as previous studies have called it [de Greck et al, 2008[de Greck et al, , 2009Kelley et al, 2002;Northoff and Bermpohl, 2004;Northoff et al, 2006;Phan et al, 2004], describes how important and how close to themselves subjects experience specific stimuli. Neurobiologically, tasks that engage the notion of self-relatedness, and hence personal relevance have implicated regions from reward circuitry such as the NACC, VTA, and the VMPFC [de Greck et al, 2008;Northoff et al, 2006;Northoff et al, 2007;Phan et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…This will be the focus in the following. Reasons of space will prevent me from giving a more general overview of the psychopathology of the self in other psychiatric disorders such as in addiction (see for instance de Greck et al [6,7]) and personality disorders (see Doering et al [8]).…”
Section: Part 1: Definition and Neuroanatomy Of The Selfmentioning
confidence: 99%